Cómo analizar una película: a propósito de La Historia Oficial - Delponti Macchione, Patricia (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2007)
Due to its powerful influence as a cultural massive industry, the cinema is one of the most important media used by pedagogues and investigators, as an essential tool to rebel the ideology of a society. However, the one who tries to investigate the philosophic roots of a film, will have to ask himself about the different aspects that take place around the movie, such as the film reception context, its influence and the polemics performed. Bearing in mind the genre to which each film belongs to and the investigator’s followed aims, the use of the Critical analysis, as a study system, is appropriate to locate the film between the creator base and the public. In this way, it is possible to discover the meaning that lies behind the cinematographic work, and its effects. The official story is a movie that shows the different ways in which the political and historical reality representation is done